Genetic determinants of susceptibility to silver nanoparticle‐induced acute lung inflammation in mice. Issue 10 (17th July 2017) - Scoville, David K.; Botta, Dianne; Galdanes, Karen; Schmuck, Stefanie C.; White, Collin C.; Stapleton, Patricia L.; Bammler, Theo K.; MacDonald, James W.; Altemeier, William A.; Hernandez, Michelle; Kleeberger, Steven R.; Chen, Lung‐Chi; et al.
ABSTRACT: Silver nanoparticles (AgNPs) are employed in a variety of consumer products; however, in vivo rodent studies indicate that AgNPs can cause lung inflammation and toxicity in a strain‐ and particle type–dependent manner, but mechanisms of susceptibility remain unclear. The aim of this study was to assess the variation in AgNP‐induced lung inflammation and toxicity across multiple inbred mouse strains and to use genome‐wide association (GWA) mapping to identify potential candidate susceptibility genes. Mice received doses of 0.25 mg/kg of either 20‐nm citrate‐coated AgNPs or citrate buffer using oropharyngeal aspiration. Neutrophils in bronchoalveolar lavage fluid (BALF) served as markers of inflammation. We found significant strain‐ and treatment‐dependent variation in neutrophils in BALF. GWA mapping identified 10 significant single‐nucleotide polymorphisms (false discovery rate, 15%) in 4 quantitative trait loci on mouse chromosomes 1, 4, 15, and 18, and Nedd4l (neural precursor cell expressed developmentally downregulated gene 4‐like; chromosome 18), Ano6 (anocatmin 6; chromosome 15), and Rnf220 (Ring finger protein 220; chromosome 4) were considered candidate genes. Quantitative RT‐PCR revealed significant inverse associations between mRNA levels of these genes and neutrophil influx. Nedd4l, Ano6, and Rnf220 are candidate susceptibility genes for AgNP‐induced lung inflammation that warrant additional exploration in future studies.—Scoville, D. K., Botta, D., Galdanes, K., Schmuck, S. C., White, C. C., Stapleton, P. L., Bammler, T. K., MacDonald, J. W., Altemeier, W. A., Hernandez, M., Kleeberger, S. R., Chen, L.‐C., Gordon, T., Kavanagh, T. J. Genetic determinants of susceptibility to silver nanoparticle‐induced acute lung inflammation in mice. FASEB J. 31, 4600–4611 (2017). www.fasebj.org